Technique variability of performance on rotational aerial skills in gymnastics - Prassas, S.; Donti, O.; Donti, A.; Ariel, G. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Elite performance is typically associated with a low level of technique variability over repeated performances. The purpose of this study was to test the variability of technique performance of an elite level gymnast performing two fundamental skills on the balance beam, salto backward, tucked (SBT) and front aerial walkover (FAW). Results showed that the gymnast was capable of performing both skills with consistency and minimal variability. Before one extrapolates this observation to all skilled performers and performances, a larger sample of athletes and skills should be tested.